2017
DOI: 10.3847/1538-4357/aa7fb6
|View full text |Cite
|
Sign up to set email alerts
|

Perpendicular Diffusion Coefficient of Comic Rays: The Presence of Weak Adiabatic Focusing

Abstract: The influence of adiabatic focusing on particle diffusion is an important topic in astrophysics and plasma physics. In the past several authors have explored the influence of along-field adiabatic focusing on parallel diffusion of charged energetic particles. In this paper by using the Unified NonLinear Transport (UNLT) theory developed by Shalchi (SH2010) and the method of He and Schlickeiser (HS2014) we derive a new nonlinear perpendicular diffusion coefficient for nonuniform background magnetic field. This … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…where subscript i denotes an axis of some Cartesian coordinate system, v is the component of the particle velocity along said axis, and the angle brackets an ensemble-averaging process. For an alternative approach of incorporating the effects of adiabatic focusing, see Wang et al (2017). In this study, a coordinate system with the z-axis along the uniform component Ideally, an exact expression for the velocity components should be employed in Equation (1).…”
Section: Perpendicular Diffusionmentioning
confidence: 99%
See 1 more Smart Citation
“…where subscript i denotes an axis of some Cartesian coordinate system, v is the component of the particle velocity along said axis, and the angle brackets an ensemble-averaging process. For an alternative approach of incorporating the effects of adiabatic focusing, see Wang et al (2017). In this study, a coordinate system with the z-axis along the uniform component Ideally, an exact expression for the velocity components should be employed in Equation (1).…”
Section: Perpendicular Diffusionmentioning
confidence: 99%
“…Due to the significance of pitch-angle scattering in the transport of SEPs, many studies focus on the pitch-angle diffusion coefficient D μμ and its role in their diffusion parallel to some mean field (e.g., Karimabadi et al 1992;Reames 1999;He & Wan 2012;Agueda & Vainio 2013). To date, however, fewer studies have focused on the pitch-angledependent Fokker-Planck perpendicular diffusion coefficient D ⊥ (see, however, Qin & Shalchi 2014;Wang et al 2017), which enters directly into the Skilling (1971) equation solved in computational studies of SEP transport and, thus, could potentially play a crucial role in studies of space weather (e.g., Schwadron et al 2014;Laitinen et al 2018). These particle transport simulations, however, have shown that calculated SEP intensities and anisotropies are sensitive to the magnitude as well as the pitch-angle dependence of this quantity (Zhang et al 2009;Dresing et al 2012;Laitinen et al 2013Laitinen et al , 2018Strauss & Fichtner 2015;Strauss et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…By introducing the linear phase space density f (z, µ, t) = f 0 (z, µ, t)/B 0 , from Equation (2), the modified Fokker-Planck equation for the distribution function of energetic charged particles can be obtained (Kunstmann 1979;He & Schlickeiser 2014;Wang et al 2017b;Wang & Qin 2018)…”
Section: Equation Of Isotropic Distribution Functionmentioning
confidence: 99%
“…With strong pitch-angle scattering, the gyro-tropic cosmic-ray phase space density f ( x, µ, t) can be split into the dominant isotropic part F( x, t) and the subordinate anisotropic part g( x, µ, t) (see, e.g., Schlickeiser et al 2007;Schlickeiser & Shalchi 2008;He & Schlickeiser 2014;Wang et al 2017b;…”
Section: Equation Of Isotropic Distribution Functionmentioning
confidence: 99%
See 1 more Smart Citation